VRSurvival Runner: Aplikasi Exergaming Survival berbasis Virtual Reality - Joe Yuan Mambu; Audrey H Siar (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
Exercising is not something that many people enjoy, and often a burden. In Indonesia, the prevalence of overweight and obesity is on a steady rise since 2013. One of the cause of these trend is the sedentary lifestyle. Lack of physical activities in this lifestyle has lead to poor cardiorespiratory fitness which proven to increase mortality rate. The purpose of this research is to create android game based on virtual reality and with the genre of exergaming. This research aims to create a new and variative ways to exercise without going out of your home dan to create a new atmosphere of exercising that is fun because of the survival horror genres. This research is using prototyping models and using Unity 3D as the game-engine that allow the application to run on Android Devices. The result of this research is VRSurvival Runner, an android game that allows the player to run, jump, to avoid zombies that are chasing the player, and also this game has a feature of counting the estimated burned calories while playing the games. A trial test on the app also has been done without any problem.